EFFECT OF DIE ADHESIVE ON THE PERFORMANCE OF HIGH-G MEMS ACCELEROMETER - GUO HuiYu; WEN Feng; KANG Qiang; SHI YunBo; WANG YanYang (Jixie qiangdu)
The sensitivity and reliability of packaged high-g MEMS accelerometer strongly depends on die attach quality that should pay special attention in the operation. A package method based on die attach is presented for a prepared MEMS high-g accelerometers by using two die attach adhesives with different elasticity modulus. The effect of the die adhesive on the performances has been studied by using finite element analysis（ FEA） and Hopkinson pressure bar measurement system simultaneously. With the consistent package process,we have experimentally demonstrated that the characteristic of dynamic sensitivity for the prepared MEMS high-g accelerometers increases with the increasing of elasticity modulus of the die attach adhesives. From this result,it is possible to fabricate MEMS high-g accelerometer with bigger sensitivity by applying die attach adhesive with bigger elasticity modulus.